The Medical-Legal Transcendence of Injuries Caused by Sports Violence from the Perspective of the Venezuelan Criminal-Legal Process (2016)
Purpose: Criminal law and sports are not subjects that can be easily, or intuitively, associated, at least at first sight. The objective of this research is to analyze from the criminal-legal perspective the possible crime of injuries resulting from sports violence and its possible sanctions. Description: Sports, like any other activity of the human being, are not exempt from conduct that can be considered criminal. The crime of injuries caused by violence in the practice of sports is a clear example that is used to explain the criminal-legal treatment that should be applied when a competitor transgresses fair play. Point of view: However, the problem arises when the common denominator in the application of criminal law to sports injuries is the administrative law-criminal law relationship, using as a vehicle the non bis in idem principle. Professional sports are subject to criminal penalties on a daily basis, but generally sports infractions are only managed administratively. Conclusions: Therefore, it is necessary to apply criminal law to situations occurring in the sports field; when an athlete has animus laendi to injure another, he shall be punished according to the Venezuelan Criminal Code.